Grey evaluation model and algorithm of network attack effectiveness - WANG Hui-mei; JIANG Liang; XIAN Ming; WANG Guo-yu (Tongxin xuebao)
Network attack effect evaluation is a complex problem especially in the operation of network attack and de-fence, in which the information is incomplete and vague.The grey system theory is a powerful tool to solve the problem which has a little and uncertain information.A grey evaluation system and model, based on the evaluation index system, was proposed and grey evaluation algorithm was introduced.Using rough set theory, the nonlinear combination weight of evaluation indices was established.A simulation example was also given, which showed that the approach was brief and effective.This approach can be used to evaluate the effectiveness of single attack, as well as to compare like kind attack, so that the attack can be sorted based on the effect evaluation.